1987
DOI: 10.1016/0014-5793(87)80837-2
|View full text |Cite
|
Sign up to set email alerts
|

Insulin increases membrane protein kinase C activity in rat diaphragm

Abstract: Calcium/phospholipid-dependent protein kinase activity (protein kinase C) was identified in rat diaphragm membrane and cytosol fractions by means of in vitro phosphorylation either of histones or of a specific 87 kDa protein substrate, combined with phosphopeptide-mapping techniques. Both insulin and tumor-promoting phorbol ester treatment of the diaphragm preparations led to increased protein kinase C activity in the membrane fractions. In contrast to the phorbol ester, however, insulin did not induce a conco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(25 citation statements)
references
References 36 publications
1
24
0
Order By: Relevance
“…To monitor membrane subfractionation, we have studied Na+/K'ATPase activity which was enriched in the 25% sucrose fraction, 5 '-nucleotidase which was enriched in the 25-30% sucrose fractions, as well as phospholemman, a recently cloned chloride channel densely distributed across all domains of sarcolemma (32,33). Previous muscle subfractionation studies (28,29,39,40) showing sarcolemmal enrichment in the 25% sucrose fraction relied heavily on Na+/K'ATPase which, in epithelial cells, is localized to specific plasma membrane domains juxtaposed to ankyrin/fodrin complexes and other elements of membrane skeleton (41).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To monitor membrane subfractionation, we have studied Na+/K'ATPase activity which was enriched in the 25% sucrose fraction, 5 '-nucleotidase which was enriched in the 25-30% sucrose fractions, as well as phospholemman, a recently cloned chloride channel densely distributed across all domains of sarcolemma (32,33). Previous muscle subfractionation studies (28,29,39,40) showing sarcolemmal enrichment in the 25% sucrose fraction relied heavily on Na+/K'ATPase which, in epithelial cells, is localized to specific plasma membrane domains juxtaposed to ankyrin/fodrin complexes and other elements of membrane skeleton (41).…”
Section: Discussionmentioning
confidence: 99%
“…Na+/K'ATPase specific activity was greatest in the 25% sucrose fraction, and enrichment of 5 '-nucleotidase was highest in the 25, 27, and 30% fractions with a lower value in the 35% fraction. Phospholemman, a chloride channel which is densely distributed across all domains of sarcolemma (32,33), was most enriched in 25, 27, and 35% sucrose fractions. Importantly, coinfusion of glucosamine compared with insulin alone did not affect enrichment of either S '-nucleotidase, Na+/K' ATPase, or phospholemman in any of the membrane subfractions (P = NS), and, therefore, glucosamine's ability to block insulin-mediated translocation of GLUT 4 could not be ascribed to changes in membrane subfractionation.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, in the presence of DAG, the concentration of Ca 2+ necessary for activation of cPKCs is in the physiological range. There is evidence for and against the possibility that insulin induces an increase in intracellular [Ca 2+ ] [29][30][31][32][33]. In newborn rat brown adipocytes it was shown that the insulininduced elevation of intracellular [Ca 2+ ] was PI3 kinase dependent [34].…”
Section: Mechanisms Of Activationmentioning
confidence: 99%
“…Src tyrosine kinase has been shown to be involved in insulin and other growth factor signaling in several cell types, including skeletal muscle [52][53][54][55][56][57][58][59][60][42][43][44][45][46][47][48][49]. Moreover, in the case of PKCs α and δ, insulin-induced tyrosine phosphorylation is apparently mediated by the Src family of tyrosine kinases, if not Src tyrosine kinase itself ( [31] and unpublished). Currently, the level of knowledge of potential tyrosine phosphorylation sites in PKCα and other PKC isoforms is quite limited, and to our knowledge, studies on their importance have yet to be performed.…”
Section: Mechanisms Of Activationmentioning
confidence: 99%
“…PKC activity was recently shown to play a role in insulin resistance in cultured cells [11][12][13]. Kim et al [14] demonstrated that membrane-bound PKC-lambda/zeta activation and decreased PI3 kinase activity are both involved in insulinmediated glucose disposal in an insulin-resistant rat model.…”
Section: Introductionmentioning
confidence: 99%